Dawn at Emberwilde - Ladd, Sarah E. (Nashville, Tennessee : Thomas Nelson, 2016)
Isabel Creston never dared to dream that love could be hers moret the edge of a forest filled with dark secrets, she faces a fateful choice between love and duty.
Keywords: Man-woman relationships -- Fiction; Upper class families -- Fiction; Surrey (England) -- Fiction -- Social life and customs -- 19th century; Christian fiction; Romance fiction